Role of Aahar and Panchakarma on restoration of euglycemia in known type II diabetes mellitus - Revandkar, Vaidehi; Gond, Bipin; Mandole, Rahul; Amin, Gurudatta; Ghadigaonkar, Pravin (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus, in particular, has emerged as a significant health concern, affecting millions of individuals and placing a considerable strain on the healthcare system. Promoting remission of diabetes, wherein patients achieve a state of sustained blood sugar control without the need for ongoing medication or with a reduced reliance on medication, can yield remarkable benefits. This study sought to understand the role of Aahar and Panchakarma on restoration of euglycemia in known type 2 diabetes patients. Methods: A retrospective, observational, cohort study was conducted at Madhavbaug Cardiac Care Clinic between April 2021 and April 2022 in Maharashtra, India. Patients aged 18 years and older with a diagnosis of type 2 diabetes mellitus with glycated haemoglobin level (HbA1c) >7% and had participated in the Comprehensive Diabetes Care (CDC) program were included in this study. Parameters such as HbA1c, body weight, body mass index (BMI), and dependence on conventional allopathic medication were assessed at the end of the CDC program. Follow-up was conducted at 90 days. Day 1 and day 90 data were compared. Results: Of the 45 patients, 17 (40.5%) patients had a negative glucose tolerance and 14 (33.3%) patients had impaired glucose tolerance. HbA1c, body weight, and BMI improved at the end of CDC program. Dependency on conventional allopathic medications was also reduced. Conclusions: Restoration of euglycemia in patients with type 2 diabetes mellitus is possible, however, further studies to understand the affecting factors are warranted.